2008
DOI: 10.1111/j.1533-2500.2008.00176.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Differences Between High‐Risk Acute vs. Chronic Low Back Pain Patients

Abstract: The present study was designed to evaluate the relative degree and type of emotional distress in high-risk acute low back pain (ALBP) subjects (defined as less than 3 months since initial injury) vs. high-risk chronic low back pain (CLBP) subjects (defined as greater than 3 months since initial injury). It is an extension of earlier findings that demonstrated the significant role that such emotional distress may play in the development of CLBP disability if not appropriately treated in the acute phase. This wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 27 publications
1
37
0
5
Order By: Relevance
“…One limitation is that the current sample may not be representative of all pain patients. This sample was composed of patients with chronic pain (patients who have not recovered 6 months after the injury), a type of pain episode that has been linked to emotional distress (Gatchel, Polatin, & Mayer, 1995;Gatchel, Bernstein, Stowell, & Pransky, 2008). Thus, the cutoffs related to this study might not generalize to patients with acute or recurrent pain conditions.…”
Section: Study Limitationsmentioning
confidence: 99%
“…One limitation is that the current sample may not be representative of all pain patients. This sample was composed of patients with chronic pain (patients who have not recovered 6 months after the injury), a type of pain episode that has been linked to emotional distress (Gatchel, Polatin, & Mayer, 1995;Gatchel, Bernstein, Stowell, & Pransky, 2008). Thus, the cutoffs related to this study might not generalize to patients with acute or recurrent pain conditions.…”
Section: Study Limitationsmentioning
confidence: 99%
“…We divided our sample into three clinically relevant groups-those with no chronic pain, those with mild chronic pain, and those with moderate-severe chronic pain-as more severe chronic pain has a greater impact on quality of life in general population samples. [41][42][43] We hypothesized that there would be an association between more severe chronic pain and: 1) depression and increased use of antidepressant medication and counseling; 2) increased use of non-opioid pain medications; and 3) use of a substance (marijuana, alcohol or cocaine) to manage pain.…”
Section: Objectivementioning
confidence: 99%
“…It has been found that emotional disorders and depression are more frequent in patients with CLBP compared to patients with acute LBP (31). The effects of pharmacologic treatment, psychotherapy, exercise, and combined physical therapy on pain, disability, and depression in patients with CLBP have been evaluated in several studies (32,33).…”
Section: Discussionmentioning
confidence: 99%